Eritrea : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This Selected Issues paper describes economic developments in Eritrea during the 1990s. The paper highlights that since the early 1990s, the Eritrean economy has recovered considerably, thanks to the rebuilding of the infrastructure and the improved availability of essential imports following major trade reforms in 1994. During 1993-96, real GDP growth averaged about 4 percent annually, ahead of the estimated population growth rate of about 3 percent. However, annual growth was erratic over the period mainly because of the drought conditions in 1993 and 1995, whereas the weather was exceptionally favorable in 1994.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet